IMPLEMENTASI PROGRAM PENGEMBANGAN USAHA MINA PEDESAAN PENGOLAHAN DAN PEMASARAN HASIL PERIKANAN (PUMP-P2HP) TAHUN 2014 DI KABUPATEN TRENGGALEK - Sari Puspitorini (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2019)
The PUMP-P2HP Program is a community-based poverty reduction program through the facilitation of business development assistance for processors and marketers of fishery products within the Processing Group and Marketers (POKLAHSAR). The purposes of this study were to describe and to analyze the Implementation of PUMP-P2HP Program 2014 in Trenggalek Regency and factors that support or inhibit  PUMP-P2HP Program. This research uses qualitative descriptive method, while collecting primary data through interview and observation, while collecting secondary data from literatures. The results of the research showed that : 1) the Implementation of PUMP-P2HP Program in 2014 in Trenggalek Regency has been referring to 6 elements of empowerment that is mentoring, community participation, group organizing, transparency, monitoring system and gender perspective; 2) Supporting success factors of the Implementation of PUMP-P2HP Program 2014 in Trenggalek Regency including good communication and coordination between the implementors, qualified human resources and adequate budget, 3) The inhibiting success factors of the PUMP-P2HP Program 2014 in Trenggalek Regency including the identification and verification of new groups for substitution of aspiration groups, causing the proposing stage up to the withdrawal.